Indie fitness gym web application / Muizzuddin Muzaini … [et al.] - Muzaini, Muizzuddin; Abdul Manan, Muhammad Amirul Azim; Asmawi, Muhammad Danial; Nor Azam, Mohamad Daniel Hakim; Mohd Mazlan, Marha Firzanah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
A gym is a favourite place for physical exercise. The most common reasons for going to the gym are build self-confidence by building muscles throughout the body, but mostly did not last long then stopped doing the exercise. Unfamiliar with equipment, Poor knowledge of training programs and diet programs is a major problem. Online platform is the world's currently most popular platform for commercials. Then, Online gym membership application was created in the gym based on a web application using CSS with PHP,Java programming language, XML and MySQLi. This application is a web application. This application offers an e-commerce system for the consumer to book a coach. Indie Fitness will register the coach and get several categories like Zumba, Bodybuilding, Weight loss and Cardio workout.Users also be able to register their own account by themself. Users are also able to choose their training program, become a member and buy gym wear accessories and protein from the web store.